2022
DOI: 10.1177/0306624x221102845
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Childhood Adversities and Their Associations With Adult Victimization Among Incarcerated Men and Women in Spanish Prisons

Abstract: Adverse childhood experiences (ACEs) are prevalent and have long lasting effects. There is evidence of gender differences in exposure to different types of ACEs, with women experiencing higher levels of sexual abuse and cumulative adversity than men. Despite this, most research examining patterns of adversities have used joint samples, assuming that men and women have comparable profiles. The current study examines if distinct profiles of childhood adversities exist for men and women and analyzes their associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…These study outcomes include unmet care coordination needs (Anyigbo et al, 2021), prenatal social networks (Napier et al, 2023), school performance (Merians et al, 2019;Stempel et al, 2017), cognitive functioning (Yuan et al, 2022), resilience/ flourishing (S. S. Chen, He, et al, 2022;L. Wang, Yu, et al, 2022), victimization and perpetration of IPV/violent behavior (Aizpurua et al, 2023;Burke et al, 2022;Lee et al, 2021;Miedema et al, 2023;Zietz et al, 2020), and offspring's socio-emotional functioning (Stargel & Easterbrooks, 2020).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These study outcomes include unmet care coordination needs (Anyigbo et al, 2021), prenatal social networks (Napier et al, 2023), school performance (Merians et al, 2019;Stempel et al, 2017), cognitive functioning (Yuan et al, 2022), resilience/ flourishing (S. S. Chen, He, et al, 2022;L. Wang, Yu, et al, 2022), victimization and perpetration of IPV/violent behavior (Aizpurua et al, 2023;Burke et al, 2022;Lee et al, 2021;Miedema et al, 2023;Zietz et al, 2020), and offspring's socio-emotional functioning (Stargel & Easterbrooks, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Other non-maltreatment family adversities were expanded such as (a) parental/guardian death (studies based on NSCH; studies using ACE-IQ; Aizpurua et al, 2023;Hemady et al, 2022;Lacey, Pinto Pereira, et al, 2020;Lacey et al, 2022;MacLochlainn et al, 2022;Miedema et al, 2023;Smith et al 2023;G. F. Wang, Yuan, et al, 2022;Xiao et al, 2023;Yu et al, 2022;Yuan et al, 2022 also added sibling death; Zhang et al, 2020;Zietz et al, 2020); (b) disadvantaged household socioeconomic status such as poverty/material hardship/financial struggles (studies based on FFCWS, NSCH; S. S. Chen, He, et al, 2022;Heidinger & Willson, 2022;Kim, Lee, et al, 2020;Yu et al, 2022), parents' unemployment (Heidinger & Willson, 2022;Zhang et al, 2020), and low maternal education (Zhang & Monnat, 2022); (c) illness/ disability/accident experienced by a family member (S. S. Chen, He, et al, 2022;MacLochlainn et al, 2022;G.…”
Section: Indicatorsmentioning
confidence: 99%
“…A few studies have explored the role of vulnerability as identified by von Hentig (1948), particularly mental illness and symptoms of psychological distress (Blitz et al, 2008;Caravaca-Sánchez & Wolff, 2016;Wolff et al, 2009;Wood, 2013;Wood & Buttaro, 2013). Research on the etiological transmission of harm over the life cycle has been pverlooked, with a few exceptions (Aizpurua et al, 2021;Caravaca-Sánchez & Wolff, 2016;Wolff et al, 2007). Moreover, these studies have traditionally been insensitive to well-known gender-based differences in victimization (Tjaden & Thoennes, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Only four published studies have estimated the risk factors associated with violence against incarcerated women without the inclusion of incarcerated men (Aizpurua et al, 2021; Caravaca-Sánchez & Wolff, 2016; Lahm, 2015; Wolff et al, 2007). The study by Lahm (2015), using data from a single women's prison, predicted four types of victimization—physical, sexual, property, and verbal—using traditional importation and deprivation covariates.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation